The TECPR1:ATG5-ATG12 complex conjugates LC3/ATG8 to damaged lysosomes that expose luminal glycans in response to osmotic imbalance - Yingxue Wang; Matthew Jefferson; Maria Ramos; Matthew Whelband; Kristin Kreuzer; Grace Khuu; Michael Lazarou; James Mccoll; James Lazenby; Cynthia B Whitchurch; Paul Verkade; Ulrike Mayer; et al. (Autophagy Reports)
Hydrolytic enzymes within lysosomes maintain cell and tissue homoeostasis by degrading macromolecules delivered by endocytosis and autophagy. The release of lysosomal enzymes into the cytosol can induce apoptosis and “lysosome-dependent cell death” making it important for damaged lysosomes to be repaired or removed. Extensive lysosome damage exposes luminal sugars to galectin-dependent autophagy pathways that use ATG16L1:ATG5-ATG12 complex to conjugate LC3/ATG8 to autophagosomes to facilitate removal by lysophagy. Sphingomyelin exposed on stressed lysosomes recruits the lysosome tethering protein TECPR1 (tectonin beta propeller repeat-containing protein) allowing an alternative TECRP1:ATG5-ATG12 complex to conjugate LC3 directly to lysosomes. Here we have used cells lacking ATG16L1 to follow the recruitment of TECPR1, galectin-3 and LC3/ATG8 to lysosomes in response to osmotic imbalance induced by chloroquine. TECPR1 was recruited to swollen lysosomes that exposed sphingomyelin. LC3II was absent from swollen lysosomes but located to small puncta that contained the V-ATPase and LAMP1. The presence of galectin-3 and PI4P in the small LC3 puncta suggested that the TECPR1:ATG5-ATG12 complex conjugates LC3 to lysosome remnants that have ruptured in response to osmotic imbalance.